2012
DOI: 10.1242/jeb.067447
|View full text |Cite
|
Sign up to set email alerts
|

An unusual myosuppressin from the blood-feeding bugRhodnius prolixus

Abstract: SUMMARYThe myosuppressin (MS) gene was cloned from a central nervous system (CNS) cDNA library of the hematophagous insect Rhodnius prolixus and is predicted to contain two introns and three exons. The mRNA transcribed from the myosuppressin gene encodes an 88 amino acid prepropeptide, which results in a mature decapeptide after post-translational modification. When compared with the myosuppressins isolated from other insects, the R. prolixus myosuppressin has a unique amino acid sequence (pQDIDHVFMRFamide), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…However, the cardioacceleratory properties of FLPs are not universal. Depending on the N-terminal sequence of the peptide, and the insect being tested, some FLPs are cardioacceletatory (Cuthbert and Evans, 1989;Robb and Evans, 1990;Duve et al, 1993;Duttlinger et al, 2003), some are cardiodeceleratory (Cuthbert and Evans, 1989;Robb and Evans, 1990;Nichols et al, 1999;Lee et al, 2012), some have complex effects that are dependent on the presence of other molecules (Nichols, 2006), and yet others have no effect on heart physiology (Duve et al, 1993;Nichols et al, 1999;Nichols, 2006). In the present study, we confirm the cardioacceleratory activity of SALDKNFMRFamide and FMRFamide, and for the first time show in a holometabolous insect that FLPs accelerate the antennal APOs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cardioacceleratory properties of FLPs are not universal. Depending on the N-terminal sequence of the peptide, and the insect being tested, some FLPs are cardioacceletatory (Cuthbert and Evans, 1989;Robb and Evans, 1990;Duve et al, 1993;Duttlinger et al, 2003), some are cardiodeceleratory (Cuthbert and Evans, 1989;Robb and Evans, 1990;Nichols et al, 1999;Lee et al, 2012), some have complex effects that are dependent on the presence of other molecules (Nichols, 2006), and yet others have no effect on heart physiology (Duve et al, 1993;Nichols et al, 1999;Nichols, 2006). In the present study, we confirm the cardioacceleratory activity of SALDKNFMRFamide and FMRFamide, and for the first time show in a holometabolous insect that FLPs accelerate the antennal APOs.…”
Section: Discussionmentioning
confidence: 99%
“…In other insects, the heart contracts in a myogenic manner (Jones, 1977;Dulcis et al, 2001;Sláma and Lukáš, 2011), but several neurohormones and neurotransmitters affect the speed and directionality of heart contractions (Johnson et al, 1997;Nichols, 2006;Lee et al, 2012;Setzu et al, 2012). Among the cardiostimulatory neurohormones is crustacean cardioactive peptide (CCAP), a cyclic amidated nonapeptide that is produced in a broad range of organisms, including crabs (Stangier et al, 1987), crayfish (Chung et al, 2006), lobsters (Chung et al, 2006), ticks (Simo et al, 2009), mites (Christie et al, 2011) and all sequenced insect lineages (Cheung et al, 1992;Furuya et al, 1993;Riehle et al, 2002;Park et al, 2003;Sakai et al, 2004;Predel et al, 2010;, which suggests that CCAP was produced by the ancestral arthropod.…”
Section: Introductionmentioning
confidence: 99%
“…The myosuppressin of R. prolixus is the first FMRFamide‐like peptide with a FMRFamide C ‐terminal motif to be found outside of the dipterans and the only myosuppressin without an FLRFamide C‐terminal motif, and even with these structural differences it is still capable of inhibiting both visceral and cardiac muscle (Lee et al ., ). Using a functional receptor assay we were able to use structural analogues of RhoprMS to help determine the importance of the methionine in position 8 and also to determine the minimum sequence needed to bind to the receptor.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, Lee et al . () have shown that RhoprMS inhibits the frequency and amplitude of contractions of the anterior midgut and hindgut, while also decreasing the heartbeat rate. These three tissues were found to express the RhoprMSR, particularly the anterior midgut, which consistently had the highest expression of the peripheral tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation